How Public Urban Space Enhance Restoration Benefits Through Combined Multisensory Effects: A Systematic Review - Wen Dong; Donghui Dai; Pengyuan Shen; Rui Zhang; Mei Liu (Land)
Rapid urbanization has heightened attention fatigue and physiological stress among urban residents. However, high-density urban construction, mainly covered by streets, squares/plazas, and buildings, in particular, poses a challenge to traditional restoration dominated by green infrasturcture. This research aims to conduct a systematic review of the available body of knowledge regarding the relationship between public urban spaces and restorativeness based on combined multisensory effects. First, a conceptual framework was proposed to connect spatial properties of public realms, sensorial mechanisms, and restoration benefits. As a result, detailed spatial elements and organization affecting multiple sensory modalities combined via additive, antagonistic, and synergistic effects were extracted, which essentially act on urban restoration, including attention, stress, and emotional recovery. Last, but not least, compared with previous research, restoration design strategies of public urban spaces accelerating multisensory integration were drawn to contribute new insights for future high-density urban development.